Identification of influenza PA-Nter endonuclease inhibitors using pharmacophore- and docking-based virtual screening. Issue 15 (15th August 2018) - Ferro, Stefania; Gitto, Rosaria; Buemi, Maria Rosa; Karamanou, Spyridoula; Stevaert, Annelies; Naesens, Lieve; De Luca, Laura
Graphical abstract: Abstract: Searching for new antiviral agents, we focused our interest on the influenza PA-Nter endonuclease. Therefore, we developed a three-dimensional pharmacophore model which contains the binding features addressed to the metal-chelating active site. The obtained hypothesis has been fruitfully employed to select three "hit compounds" through an in silico screening campaign on our in-house database of small molecules. We studied the binding poses of these hit compounds using molecular docking, and subjected them to an enzymatic assay with recombinant PA-Nter endonuclease. Compound20 proved the most active inhibitor of the endonucleolytic cleavage reaction, with an IC50 value of 12 μM.